Pemberdayaan Masyarakat dalam Pengembangan Ekowisata Berkelanjutan di Desa Wisata Kandri, Kota Semarang - Lina Nur Inayah; Tri Suminar (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This study aims to examine sustainable ecotourism strategies in developing Kandri Tourism Village, Gunungpati District, Semarang City, focusing on community empowerment, challenges faced, and the utilization of natural and cultural potential. Using descriptive research with a qualitative approach, data was collected through interviews, observation, and documentation. The results showed significant success in community empowerment, utilizing natural and cultural potential, and maintaining sustainability. The active participation of the community, from the management to MSME players and tour guides, is the main foundation that encourages collective enthusiasm in maintaining cleanliness, hospitality, and preserving local wisdom and cultural arts. Although theoretical understanding of ecotourism is uneven, practical involvement in activities and consistent training from the government, tourism office, association, and university has substantially increased the capacity of the community. The Pandanaran and Sukomakmur Tourism Awareness Groups (Pokdarwis) play a central role in triggering economic turnover and increasing local income. Commitment to environmental sustainability is also strong, as evidenced by the spring conservation program, tree planting, and waste bank plan. Government support focuses on human resource capacity building and institutional strengthening, ensuring the sustainability of ecotourism management. The utilization of natural and cultural potential is integrated through eco-tourism on plantation land, livestock, and religious sites such as Gua Kreo and Sendang. Annual cultural traditions have proven capable of attracting thousands of visitors, demonstrating the significant appeal of preserving local wisdom. Overall, ecotourism in Kandri Tourism Village succeeds in creating harmony between physical attractiveness, social and environmental sustainability, with adaptation to change and positive interaction between the community and tourists.